HUBUNGAN KOMUNIKASI EFEKTIF DAN RESPON TIME TERHADAP KEPUASAN PENGGUNA LAYANAN PUBLIC SAFETY CENTER (PSC) 119 - Abdullah, Abdullah; Meilando, Rizky; Nurvinanda, Rezka (Ensiklopedia of Journal, 2025)
Public satisfaction with PSC 119 services is one of the important indicators in assessing service effectiveness. High public satisfaction with PSC 119 services has a positive impact not only on the reputation of the service, but also on the effectiveness of handling emergency cases. Several factors that influence this satisfaction include the speed of response (response time) and the quality of effective communication carried out by PSC 119 officers. This study aims to determine the relationship between effective communication and response time on the satisfaction of users of the Public Safery Center (PSC) 119 Bangka Selatan service in 2024. This study uses a cross-sectional study design. This study was conducted by distributing questionnaires to 66 users of the PSC 119 Bangka Selatan service on November 6 - December 2, 2024. The data collected were then analyzed univariately and bivariately using the chi-square test.The results of this study prove that there is a relationship between effective communication factors (p-value = 0.000), and response time (p-value = 0.000) on the satisfaction of users of the Public Safery Center (PSC) 119 South Bangka services in 2024. It is hoped that PSC 119 South Bangka Regency can conduct routine training for nurses related to effective communication, including listening skills, empathy, and clear explanations of medical procedures.Keywords : User Satisfaction, Effective Communication, Public Safety  Center, Response Time